The Effect of Immersion Depth and the Distance Between Copper and Zinc Electrodes on the Potential Difference Generated in an Experiment Using a Saltwater Electrolyte Battery - Hartaya Hartaya; Jarot Delta Susanto; Mohamad Ridwan (Meteor STIP Marunda, 2023)
The demand for energy continues to rise alongside today’s technological advancements, particularly the need for electricity generated from environmentally friendly sources. Saltwater can serve as an alternative energy source—a medium used to generate electricity that is relatively inexpensive, readily available, and non-hazardous. Saltwater commonly encountered in daily life is NaCl, or what is commonly known as table salt. By constructing a simple voltaic cell, an experiment was conducted to determine the extent to which variations in immersion depth and the distance between the two electrodes in the saltwater electrolyte affect the reaction with the electrodes in generating an electric potential difference. This experiment used two different electrodes: copper (Cu) as the cathode and zinc (Zn) as the anode. The saltwater electrolyte used also varied in salt concentration. It is hoped that the results of this study can be utilized by the public to help provide an alternative source of electrical energy and reduce monthly electricity bills.